Evaluating instructional labs’ use of deliberate practice to teach critical thinking skills - Emily M. Smith (American Physical Society, 2020)
The goals for lab instruction are receiving critical attention in the physics education community due to multiple reports and research findings. In this paper, we describe a theoretically motivated scheme to evaluate instructional lab curricula and apply that scheme to three implementations of an electricity and magnetism lab curriculum. The scheme has three components: (1) that critical thinking is a context-dependent process for using critical thinking skills to make evidence-based decisions (2) that to make decisions one must have agency and (3) that deliberate practice can be used to effectively teach critical thinking skills. We use this scheme to evaluate the lab instructions for three sets of instructional labs for their use of deliberate practice for teaching critical thinking skills through varied opportunities for students to exercise agency in making decisions about experiments. Our analysis shows that our curricular design did target the experimentation-focused critical thinking skills, but did not strongly align with theoretical recommendations for deliberate practice. The results provide suggestions for improvements to curricular design. For curriculum developers, instructors, and researchers who intend to teach critical thinking in the context of experimental physics, this scheme serves as a tool to create and evaluate lab instructions in terms of the ways in which specific skills are supported through deliberate practice.